FACTORS ASSOCIATED WITH NON-ADHERENCE TO PAP SMEAR TESTING: THE INFLUENCE OF SOCIODEMOGRAPHIC AND CLINICAL CONDITIONS - Scremin, Marlete; Carl Silva, Jean; Souza Guerrer, Lara; Romanovicz Hemquemeier, Rayani; Clara Guimarães Justo Pereira, Ana; Eyng dos Santos, Beatryz; Alencar Froes, Karine; Clara Lélis Ramos Cardoso, Maria; Rennan Soares Barbosa, Richard; Gonçalves Silva, Dinariam; Victor Souza de Brito, Lauro; Cecília Fonseca de Souza e Silva, Maria; et al. (Revista Gênero e Interdisciplinaridade, 2026)
The present study aimed to analyze the factors associated with non-adherence to cervical cancer screening. An integrative literature review was conducted, and articles retrieved from the secondary databases Virtual Health Library, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online, and Online System for Searching and Analyzing Medical Literature were analyzed using the keywords Pap smear test; primary health care; and basic care. The main factors identified are individual factors: fear, embarrassment, pain, discomfort, lack of knowledge about the exam; sociodemographic factors: low education, low income, race/color, multiparity; and service-related factors: difficulty of access (schedules, transportation), poor infrastructure, lack of supplies, delays in delivering results, and weak connection with the healthcare professional. The analysis of factors associated with non-adherence to cervical cancer screening (Pap smear) revealed a complex intersection of barriers that need to be addressed in order to increase coverage rates and, consequently, reduce morbidity and mortality from this neoplasm.